Predation by great skuas at a large Shetland seabird colony - Votier, S.C.; Bearhop, S.; Ratcliffe, N.; Phillips, R.A.; Furness, R.W. (Journal of Applied Ecology, 2004)
1. Skuas are top predators in marine ecosystems and may have detrimental effects on seabird communities they prey upon. However, predation rates are poorly understood and poorly quantified. Using a bio-energetics model we estimate seabird predation by great skuas, Stercorarius skua , at a large UK colony (Hermaness, Shetland). We investigate the influence of dietary specialization and fishery management on predation and explore the effect of experimental removal of specialist bird predators. 2. Great skuas at Hermaness required 491.5 x 10(6) kJ and 546.6 x 10(6) kJ of energy in each of two breeding seasons. Breeding skuas fell into one of two groups: a small proportion (5%) of specialist bird predators or the vast majority (95%) that fed opportunistically on birds or specialized on fishery discards. During 1999, great skuas consumed approximate to80 000 kg of fish, which increased to over 90 000 kg in 2001. About 13 000 seabirds were consumed by great skuas each year, with 26-29% being consumed by specialist bird predators. 3. Although it is difficult to assess, great skuas appear to be having a negative impact on seabird populations. Altering model inputs to test differing scenarios revealed that reductions in fishery discards would result in increased seabird predation rates. However, proposed changes in fishery management over the period of the study did not reduce discarding rates, which instead increased. 4. Synthesis and applications . The use of a bioenergetics model reveals that great skua predation may negatively affect seabird populations. Availability of fishery discards is an important factor influencing seabird predation rates, but predicting the effect of changes in fishery management may be difficult in the short term. Specialist bird predators consume large quantities of seabird prey, but this is less significant at the population level. Although experimental removal of specialist bird predators may reduce predation at a minimal loss of skuas, it is unclear whether conspecifics may replace them ...